An LMI based scheduling algorithm for constrained stabilization problems - Wada, N.; Saeki, M. (Systems & control letters, 2008)
We propose a gain-scheduling control algorithm for locally stabilizing a discrete-time linear system with input saturation. The proposed control law has a structure that a high-gain control law and a low-gain control law are interpolated by using a single scheduling parameter. The scheduling parameter is computed on-line by solving a convex optimization problem with LMI constraints.